Comparison of neutrophil-to-lymphocyte ratio and mean platelet volume in the prediction of adverse events after primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction. (July 2018) - Machado, Guilherme Pinheiro; Araujo, Gustavo Neves de; Carpes, Christian Kunde; Lech, Mateus; Mariani, Stefani; Valle, Felipe Homem; Bergoli, Luiz Carlos Corsetti; Gonçalves, Sandro Cadaval; Wainstein, Rodrigo V.; Wainstein, Marco V.
Abstract: Background and aims: Elevated neutrophil-to-lymphocyte ratio (NLR) and mean platelet volume (MPV) are indirect inflammatory markers. There is some evidence that both are associated with worse outcomes in ST-segment elevation myocardial infarction (STEMI) after primary percutaneous coronary intervention (PCI). The aim of the present study was to compare the capacity of NLR and MPV to predict adverse events after primary PCI. Methods: In a prospective cohort study, 625 consecutive patients with STEMI, who underwent primary PCI, were followed. Receiver operating characteristic (ROC) curve analysis was performed to calculate the area under the curve (AUC) for the occurrence of procedural complications, mortality and major adverse cardiovascular events (MACE). Results: Mean age was 60.7 (±12.1) years, 67.5% were male. The median of NLR was 6.17 (3.8–9.4) and MPV was 10.7 (10.0–11.3). In multivariate analysis, both NLR and MPV remained independent predictors of no-reflow (relative risk [RR] = 2.26; 95%confidence interval [95%CI] = 1.16–4.32; p  = 0.01 and RR = 2.68; 95%CI = 1.40–5.10; p  < 0.01, respectively), but only NLR remained an independent predictor of in-hospital MACE (RR = 1.01; 95%CI = 1.00–1.06; p  = 0.02). The AUC for in-hospital MACE was 0.57 for NLR (95%CI = 0.53–0.60; p  = 0.03) and 0.56 for MPV (95%CI = 0.52–0.60; p  = 0.07). However, when AUC were compared with DeLong test, there was no statistically significant difference for these outcomes ( p  > 0.05). NLR had an excellent negative predictive value (NPV) of 96.7 for no-reflow and 89.0 for in-hospital MACE. Conclusions: Despite no difference in the ROC curve comparison with MPV, only NLR remained an independent predictor for in-hospital MACE. A low NLR has an excellent NPV for no-reflow and in-hospital MACE, and this could be of clinical relevance in the management of low-risk patients. Highlights: NLR and MPV are inflammation markers obtained by a simple total blood count. NLR and MPV were independent predictors of procedural adverse events. NLR was an independent predictor of in-hospital major adverse cardiovascular events (MACE). A low NLR value has an excellent negative predictive value for these outcomes.